Motivated for teaching? Associations with school goal structure, teacher self-efficacy, job satisfaction and emotional exhaustion. (October 2017) - Skaalvik, Einar M.; Skaalvik, Sidsel
Abstract: We analyzed relations between teachers' perception of the school goal structure, workload, self-efficacy, emotional exhaustion, job satisfaction, and motivation to leave the teaching profession. Participants were 760 Norwegian teachers from grade 1 to 10. Data were analyzed using confirmatory factor analysis and structural equation modeling. We found two main routes to motivation to leave, one from the perception of a learning goal structure via teacher self-efficacy and job satisfaction, leading to lower motivation to leave, and another from the perception of a performance goal structure via increased workload and emotional exhaustion, leading to higher motivation to leave. Highlights: We measured teacher perception of the school goal structure. A learning structure predicted lower motivation to leave the teaching profession. This association was mediated through higher self-efficacy and job satisfaction. A performance structure predicted higher motivation to leave the profession. This association was mediated through higher workload and emotional exhaustion.